The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.7759/cureus.40683
|View full text |Cite
|
Sign up to set email alerts
|

Incidental Finding of Riedel’s Lobe of the Liver and Intrahepatic Cholangiocarcinoma

Abstract: Riedel's lobe is a rare anatomical variant of the liver morphology with a downward tongue-like projection of the anterior edge of the right lobe. It is usually detected incidentally with abdominal imaging performed for other indications. We present a case where we found Riedel's lobe incidentally, with invasive adenocarcinoma arising from close proximity. A 64-year-old female came in with encephalopathy and was found to have a distended abdomen with tenderness. Imaging revealed a complex lobular mass in the ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…In cases of isolated metastatic lesions in Riedel's lobe, resection is a possible option [13,28]. A few cases of primary malignant tumors or metastases to Riedel's lobe have been described [32][33][34]: Soo et al reported on a Riedel's lobe metastasis from a ductal breast cancer [32]; Zamfir et al observed a case of a 65-year-old woman with primary hepatocellular Significance of Riedel's Lobe in Ovarian Cancer Surgery Riedel's lobe can be confused with an enlarged lymph node or an unidentified abdominal mass on various imaging techniques. In cases of isolated metastatic lesions in Riedel's lobe, resection is a possible option [13,28].…”
Section: Significance Of Riedel's Lobe In Ovarian Cancer Surgerymentioning
confidence: 99%
See 3 more Smart Citations
“…In cases of isolated metastatic lesions in Riedel's lobe, resection is a possible option [13,28]. A few cases of primary malignant tumors or metastases to Riedel's lobe have been described [32][33][34]: Soo et al reported on a Riedel's lobe metastasis from a ductal breast cancer [32]; Zamfir et al observed a case of a 65-year-old woman with primary hepatocellular Significance of Riedel's Lobe in Ovarian Cancer Surgery Riedel's lobe can be confused with an enlarged lymph node or an unidentified abdominal mass on various imaging techniques. In cases of isolated metastatic lesions in Riedel's lobe, resection is a possible option [13,28].…”
Section: Significance Of Riedel's Lobe In Ovarian Cancer Surgerymentioning
confidence: 99%
“…In cases of isolated metastatic lesions in Riedel's lobe, resection is a possible option [13,28]. A few cases of primary malignant tumors or metastases to Riedel's lobe have been described [32][33][34]: Soo et al reported on a Riedel's lobe metastasis from a ductal breast cancer [32]; Zamfir et al observed a case of a 65-year-old woman with primary hepatocellular A few cases of primary malignant tumors or metastases to Riedel's lobe have been described [32][33][34]: Soo et al reported on a Riedel's lobe metastasis from a ductal breast cancer [32]; Zamfir et al observed a case of a 65-year-old woman with primary hepatocellular carcinoma arising from her Riedel's lobe. The lobe was resected with "en-block" cholecystectomy [33].…”
Section: Significance Of Riedel's Lobe In Ovarian Cancer Surgerymentioning
confidence: 99%
See 2 more Smart Citations